THE IMPACT OF ONLINE CUSTOMER REVIEWS ON BRAND REPUTATION - Saidmunirxon, Axrorov; Furqon, Chairul; Hendrayati, Heny; Qudratov, Inomjon (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
This article investigates the influence of online customer reviews on brand reputation within digital marketplaces. The study employs a Systematic Literature Review informed by PRISMA 2020, synthesising peer-reviewed publications from 2015 to 2025, indexed in Scopus, Web of Science, ScienceDirect, and Google Scholar. The review shows that review valence, review volume, credibility, authenticity, helpfulness, reviewer expertise, managerial responses, and platform governance have the biggest and most consistent effects on brand reputation. Positive, detailed, and trustworthy reviews boost perceived quality, trust, and legitimacy. On the other hand, negative, suspicious, or inconsistent reviews can quickly hurt a brand's reputation. The results also show that quick and responsible responses from managers can protect a company's reputation, while suspicions of fake reviews and poor platform moderation can hurt both review trust and brand trust. In general, online reviews are no longer just a side note; they are now a key part of a company's reputation that they need to manage carefully.